Prone position in the mechanical ventilation of acute respiratory distress syndrome children: a systematic review and meta-analysis - Qin, Wen; Mao, Lei; Shen, Yue; Zhao, Li (Frontiers in Pediatrics, 2024)
Background Prone position has been well recognized for the treatment of adult acute respiratory distress syndrome (ARDS). We aimed to evaluate the role of prone position in the mechanical ventilation in children with ARDS, to provide evidence to the treatment and care of children with ARDS. Methods We searched the Pubmed et al. databases by computer until January 23, 2024 for randomized controlled trials (RCTs) on the role of prone position in the mechanical ventilation in children with ARDS. We evaluated the quality of included studies according to the quality evaluation criteria recommended by the Cochrane library. RevMan 5.3 software was used for meta-analysis. Results 7 RCTs involving 433 children with ARDS were included. Meta-analysis indicated that prone position is beneficial to improve the arterial oxygenation pressure [MD = 4.27 mmHg, 95% CI (3.49, 5.06)], PaO2/FiO2 [MD = 26.97, 95% CI (19.17, 34.77)], reduced the oxygenation index [MD = −3.52, 95% CI (−5.41, −1.64)], mean airway pressure [MD = −1.91 cmH2O, 95% CI (−2.27, −1.55)] and mortality [OR = 0.33, 95% CI (0.15, 0.73), all P < 0.05]. There were no statistical differences in the duration of mechanical ventilation between the prone position group and control group [MD = −17.01, 97.27, 95% CI (−38.28, 4.26), P = 0.12]. Egger test results showed that no significant publication bias was found (all P > 0.05). Conclusions Prone position ventilation has obvious advantages in improving oxygenation, but there is no significant improvement in the time of mechanical ventilation in the treatment of children with ARDS. In the future, more large-sample, high-quality RCTs are still needed to further analyze the role of prone position in the mechanical ventilation in children with ARDS.